A Study on Histomorphological Spectrum in Abnormal Uterine Bleeding at a Tertiary Care Center - Santharam M; Preethi Sekar; Karthikeyan TM; Sharanya Kandaswamy (National Board of Examinations Journal of Medical Sciences)
Introduction: A common gynecological problem that affects women, especially throughout their reproductive and perimenopausal years, is abnormal uterine bleeding (AUB). It includes any alteration in frequency, length, or volume that deviates from typical menstrual rhythms. The PALM-COEIN approach, which incorporates both non-structural factors like coagulopathy and ovulatory dysfunction as well as structural causes including polyps, adenomyosis, leiomyoma, and cancer, is used by the International Federation of Gynecology and Obstetrics (FIGO) to categorize AUB. For chronic AUB that does not respond to conservative management, hysterectomy is still the only effective option. For a precise diagnosis, histopathological examination (HPE) of hysterectomy tissues is essential, particularly in cases where imaging alone cannot provide a definitive answer. Materials and Methods: This retrospective cross-sectional study was conducted in the Department of Pathology at KMCH Institute of Health Sciences and Research from July 2023 to June 2024. A total of 150 reproductiveage, peri-menopausal, and post-menopausal women with complaints of abnormal uterine bleeding (AUB) who underwent hysterectomy were included in the study. Results: The most common histopathological finding was uterine fibroids, observed in 45.3% of cases, followed by adenomyosis in 19.3%. Among the endometrial abnormalities, non-secretory endometrium and disordered proliferative endometrium were identified in 31.3% and 27.35% respectively. Ultrasonography was effective in detecting fibroids but showed limited sensitivity in diagnosing adenomyosis, which was better confirmed through histopathology. Conclusion: Histopathological evaluation plays a vital role in diagnosing the causes of AUB, particularly in cases where imaging does not provide clear results.